편의점 도시락의 식단형태별, 가격대별, 편의점 브랜드별 영양성분 함량 평가 - 박진선(Jin-Seon Park); 한영희(Young-Hee Han); 현태선(Taisun Hyun) (Korean journal of community nutrition, 2020)
Objectives: This study investigated the menu and nutritional contents of convenience store lunchboxes, and evaluated the nutritional content by meal type, price, and store brand. Methods: In September 2019, 93 convenience store lunchboxes from the top five franchise stores were purchased. Relevant information on price, food weight, food ingredients, cooking methods, and nutrition labeling were subsequently collected. Nutritional content was evaluated based on the daily value (DV) and Index of Nutritional Quality (INQ), and energy contribution of carbohydrate, protein, fat, saturated fat and sugar was compared with the recommended range. Results: Most lunchboxes included the food groups; grains/starches, meats/fish/eggs/legumes, and vegetables. However, none provided fruits, and only a few lunchboxes provided milk/milk products. Stir-frying, deep-frying, and pan-frying were the most frequent methods of cooking. The average energy content of the lunchboxes was 736.6 kcal, whereas the average contents of protein, fat and saturated fat were higher than 40% of the DV, and sodium content was 66.8% of the DV. The contents of most nutrients in traditional type lunchboxes were higher, as compared to nutrients in onedish type lunchboxes. Considering pricing of lunchboxes, protein and sodium contents were higher in the higher-priced lunchboxes as compared to lower-priced lunchboxes, but there were no differences in the INQs. The contents of energy, protein, fat, saturated fat, and cholesterol significantly differed by brand. Conclusions: Our results indicate that convenience store lunchboxes contain high levels of protein, fat, saturated fat, and sodium. The nutritional contents differed by meal type, price, and store brand, and higher price did not imply higher nutritional quality. We propose the need to educate consumers to check nutrition labels and purchase appropriate lunchboxes. Manufacturers also need to make efforts to reduce the amounts of fat, saturated fat, and sodium, and not provide protein in excess.